Systematic Literature Review of Project Management Maturity Models - Ruiz-Lopez, Francisco; Ortiz-Hernandez, Javier; Bonjour, Eric; Micaelli, Jean-Pierre; Hernández, Yasmín (Programming and computer software, 2024)
Project management is a field that has been applied in various areas of knowledge, particularly in engineering and software development. For organizations, projects are a central element for generating value. They allow to reach the organizational goal by using specific methodologies, tools and software. One of the most recognized tools, even in other fields of knowledge, for its impact on process improvement is maturity models. These models have already begun to be implemented in project management. Project management maturity models are useful tools to evaluate the management process using a process reference (e.g., PMBOK). This process reference describes the best practices to achieve success in projects. The purpose of this paper is the identification of research papers that present maturity models specifically for project management. A useful classification for project managers using maturity models in a project management context is generated from the results of the review. The proposed classification considers 4 categories: (1) project management, (2) organizational performance of project management, (3) project management for specific areas, and (4) project management process in organizations. Each category classifies the project management maturity models according to their characteristics.